Paclitaxel – a Product of Fungal Secondary Metabolism or an Artefact?# - Gärditz, Klaus Ferdinand; Czesnick, Hjördis (Planta Medica, 2024)
Taxol (common name: paclitaxel) is an extremely important component of drugs for the treatment of various cancers. Thirty years after the discovery of its effectiveness, a metabolic precursor of Taxol (10-deacetylbaccatin III) is still primarily extracted from needles of European yew trees. In order to meet the considerable demand, hopes were pinned on the possibilities of biotechnological production from the very beginning. In 1993, as if by chance, Taxol was supposedly discovered in fungi that grow endobiotically in yew trees. This finding aroused hopes of biotechnological use to produce fungal Taxol in large quantities in fermenters. It never came to that. Instead, a confusing flood of publications emerged that claimed to have detected Taxol in more and more eukaryotic and even prokaryotic species. However, researchers never reproduced these rather puzzling results, and they could certainly not be applied on an industrial scale. This paper will show that some of the misguided approaches were apparently based on a seemingly careless handling of sparse evidence and on at least questionable publications. Apparently, the desired gold rush of commercial exploitation was seductive. Scientific skepticism as an indispensable core of good scientific practice was often neglected, and the peer review process has not exerted its corrective effect. Self-critical reflection and more healthy skepticism could help to reduce the risk of such aberrations in drug development. This article uses this case study as a striking example to show what can be learned from the Taxol case in terms of research ethics and the avoidance of questionable research practices.
Keywords: Taxus brevifolia; Taxus baccata; Taxus; Taxaceae; Taxol; paclitaxel; good scientific practice; research integrity